Perbedaan Moral Siswa Ditinjau dari Pembelajaran Akidah Akhlak dengan Pendekatan Kontekstual dan Tingkat Kedisiplinan Siswa di MTS Negeri 3 Tidore Kota Tidore Kepulauan - Karim, Amalia; Muhammad, Muhammad; Abbas, Sukardi; Malaka, Muhlis; Alhadar, Muhdi; Agus, Agus; Ahmad, Samlan Hi (Lembaga Teewan Journal Solutions, 2026)
This experimental study was conducted at MTs Negeri 3 Tidore with the aim of analyzing differences in students’ moral outcomes based on learning approaches and discipline levels, as well as examining their interaction. Specifically, the study compares students who received aqidah akhlak instruction through a contextual approach with those taught using a conventional approach, and also distinguishes between students with high and low discipline levels. A quantitative method with a quasi-experimental 2×2 factorial design was applied. The sample consisted of 80 eighth-grade students selected through purposive sampling, divided into experimental and control groups. Data were collected using a Likert-scale questionnaire and analyzed through two-way ANOVA. The findings indicate that there is no significant difference in students’ moral outcomes between contextual and conventional learning approaches (Sig. = 0.120 > 0.05). However, student discipline shows a significant effect on moral development (Sig. = 0.000 < 0.05), with highly disciplined students demonstrating better moral behavior. Furthermore, no significant interaction was found between the learning approach and discipline level (Sig. = 0.462 > 0.05), suggesting that the influence of discipline on moral outcomes operates independently of the teaching approach used.